The Power of Faith and Social Media in Healing Women’s Mental Health – A Theological Study - Ahmad Salman Farid (Pharos Journal of Theology)
This study investigates the profound interplay between social media engagement and spirituality in the journey of women overcoming anxiety and depression. With these pervasive mental health challenges affecting countless lives, understanding effective coping mechanisms becomes imperative. By intertwining the realms of digital connectivity and spiritual practices, this research explores how women navigate their mental health struggles, find support networks, and cultivate resilience. Drawing on a mixed-methods approach, this study delves into the experiences of a diverse cohort of women, capturing both quantitative data on social media usage patterns and qualitative insights into the significance of spirituality in their mental well-being. Through surveys, interviews, and content analysis, the multifaceted impact of social media platforms and spiritual beliefs on mental health outcomes is illuminated. The results reveal a complex landscape wherein social media serves as both a source of distress and a platform for connection and support. Moreover, spirituality emerges as a profound resource for coping, offering solace, hope, and a sense of purpose to women navigating the depths of anxiety and depression. Statistical analysis underscores the significant correlations between certain social media behaviors and mental health outcomes, while qualitative narratives enrich our understanding of the deeply personal and transformative role of spirituality in women's lives.